Faktor-Faktor Pendukung Dan Penghambat Dalam Menghafal Al-Qur’an - Dahliati Simanjuntak (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2021)
In this life, there is no achievement without trials and tribulations. With these tests and trials will be found and determined who wins and who loses. Similarly, in memorizing the Qur'an, it becomes a necessity that there are tests and trials that will distinguish the achievements of one person from another and determine the final results achieved by each of them. The problems of students in memorizing can be distinguished into problems that come from within (internal) and problems that come from outside (external). Internal problems in the form of many disobediences, feeling lazy, impatient, hopeless, memorized verses forgetting again, difficulty managing time, physical and spiritual fatigue. Meanwhile, external problems are related to the relationship between students and the physical and social environment. The physical environment of the pesantren such as room conditions, lighting, air circulation and cleanliness. While the social environment such as relationships  with  friends,  parents,  teachers  and  caregivers.  Problems  that  can  often hinder someone from memorizing the Qur'an include problems that come from within (internal factors) and problems that come from outside (external factors).